2010
DOI: 10.1146/annurev-phyto-073009-114439
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Plant and Free-Living Nematodes in Natural and Agricultural Soil

Abstract: Nematodes are aquatic organisms that depend on thin water films to live and move within existing pathways of soil pores of 25-100 mum diameter. Soil nematodes can be a tool for testing ecological hypotheses and understanding biological mechanisms in soil because of their central role in the soil food web and linkage to ecological processes. Ecological succession is one of the most tested community ecology concepts, and a variety of nematode community indices have been proposed for purposes of environmental mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
224
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(256 citation statements)
references
References 147 publications
2
224
1
6
Order By: Relevance
“…The tractability and conserved genes of many nematode species have supported the significance of their ultrastructure studies which enable their use as models for diverse biological processes; including human diseases, aging, immunity, development, ecology, evolution, and host-bacterial interactions (Aboobaker and Blaxter 2000;Couillault and Ewbank 2002;Goodrich-Blair and Clarke 2007;Mitreva et al 2009;Markaki and Tavernarakis 2010;Neher 2010;Xu and Kim 2011). Also, ultrastructural and immunolocalization of two isoenzymes, Glutathione-Stransferase (GST1) and (GST2) were carried out using immunogold electron microscopy.…”
Section: Implications Of Nematodes Ultrastructural Studiesmentioning
confidence: 99%
“…The tractability and conserved genes of many nematode species have supported the significance of their ultrastructure studies which enable their use as models for diverse biological processes; including human diseases, aging, immunity, development, ecology, evolution, and host-bacterial interactions (Aboobaker and Blaxter 2000;Couillault and Ewbank 2002;Goodrich-Blair and Clarke 2007;Mitreva et al 2009;Markaki and Tavernarakis 2010;Neher 2010;Xu and Kim 2011). Also, ultrastructural and immunolocalization of two isoenzymes, Glutathione-Stransferase (GST1) and (GST2) were carried out using immunogold electron microscopy.…”
Section: Implications Of Nematodes Ultrastructural Studiesmentioning
confidence: 99%
“…Shown below are the correlations between B (bacterial biomass), F (fungal biomass), Nb (the density of bacterivorous nematodes), Nh (the density of herbivorous nematodes), Nf (the density of fungivorous nematodes), Np (the density of predatory nematodes), No (the density of omnivorous nematodes), Col (the density of Collembola), Ori (the density of oribatid mites), Pre (the density of predatory mites), LM (Litter mass), LC (Litter total carbon), LN (Litter total nitrogen), LCN (Litter C:N ratios), SOC (Soil organic carbon), TSN (Total soil nitrogen), and SCN (Soil C:N ratios). could be regulated by bottom-up, top-down, or both and called for a quantification of the strength of the relationships among trophic levels (Neher, 2010). Also, another review paper based on a meta-analysis of global data showed that coniferous forest soils had the greatest fungal to bacterial ratios, whereas soils from deserts and grasslands had the lowest (Fierer et al, 2009).…”
Section: Top-down Vs Bottom-up Forces and Bacterial Vs Fungal Enermentioning
confidence: 99%
“…The family Criconematidae was not found in samples from Aveiro, Coimbra, Lisboa and Porto, and Hoplolaimidae was not found in samples from Lisboa. Tillage and vegetation are among the most important factors for shaping nematode assemblages in agricultural soils (Neher 2010;Neher et al 2005). However, these can be little imputed to explain differences in the nematode composition found since all the studied soils were sampled from potato fields cropped using similar cultural practices.…”
Section: Trophic Group Familymentioning
confidence: 99%
“…Monoculture agriculture or long-term exposures to soil polluted with heavy metals are regarded as types of chronic disturbances which can lead to gradual species extinction and eventually decreases resiliency of an ecosystem to disturbance or disruption (Neher 2010;Park et al 2011). In addition, some groups of organisms, such as soil nematodes, are very responsive to plant cover, land use change and chronic disturbance and are regarded as biological indicators of soil health (Yeates et al 1993).…”
mentioning
confidence: 99%